MADRASAH HEAD'S STRATEGY IN IMPROVING STUDENT DISCIPLINE - Kurniyawan, Hendi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This article discusses the strategies implemented by the Principal to improve student discipline at Madrasah Aliyah Nurul Jadid (MANJ), Probolinggo Regency, East Java Province. Using a qualitative approach, this research explores various strategies based on the leadership principles of Rasulullah SAW, personal approach, socialization of rules, respect for disciplined students, and parental involvement. Research findings show that these strategies, such as attendance before learning, monitoring student attendance, and consistent application of sanctions, have succeeded in creating a strong and sustainable culture of discipline in schools. However, the challenges that arise regarding parental intervention require a more proactive approach, such as through open communication and discussion forums. Although there is no quantitative data to support claims of reduced student offending, this provides a positive indication of the effectiveness of the strategies implemented. Therefore, continuous efforts to improve student discipline need to be made through regular evaluations and strategy adjustments according to future needs, in order to create an educational environment that is disciplined, productive, and supports students' holistic development.